2017
DOI: 10.1111/joss.12309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a warm‐up sample on stabilizing the performance of untrained panelists in time–intensity evaluation

Abstract: To improve the reliability of sensory evaluation, it is necessary to minimize response bias. In this study, we investigated the effect of a warm‐up sample on time–intensity evaluation of after‐flavor. Untrained panelists evaluated continuously perceived intensity of bitterness and retronasal aroma, using four types of samples (two brands of coffee beverages × two types of lids). Half of participants evaluated bitterness intensity in the first session and retronasal aroma intensity in the second session, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…Their results demonstrated that when the participant continuously evaluated retronasal aroma intensity in the first and second sessions and bitterness intensity in the first session, TI curve was significantly lower in the first trial than in the subsequent trials. Accordingly, the results of this study reproduced the effect of a warm-up sample in TI evaluation of retronasal aroma, as observed in the previous study [ 43 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Their results demonstrated that when the participant continuously evaluated retronasal aroma intensity in the first and second sessions and bitterness intensity in the first session, TI curve was significantly lower in the first trial than in the subsequent trials. Accordingly, the results of this study reproduced the effect of a warm-up sample in TI evaluation of retronasal aroma, as observed in the previous study [ 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…Some sensory evaluations reported that the use of a warm-up sample improves the perceptual sensitivity of the participant [ 78 , 79 , 80 ]. Gotow and colleagues [ 43 ] investigated the effect of a warm-up sample in TI evaluation of retronasal aroma and bitterness after swallowing coffee beverages. Half of the participants continuously evaluated retronasal aroma intensity over four trials in the first session, and bitter intensity over four trials in the second session.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations